Métissage de langues et transgression dans le langage des cités - Ilhem Kazi-Tani; Zakia Lounis (Carnets)
We want to demonstrate throughout this study that Djaidani’s aesthetic style in his novel Boomkeur is characterized by transgression in relation to language and aesthetic standards. In fact, the novel, which belongs to the so called “Beur Literature”, marks twists on several levels: at the aesthetic level where the rules of writing are subverted, and at the linguistic level by a fusion of languages and a melting of ordinary linguistic expressions. Can this transgression be read as a reaction to a superior dominant culture?